Student outcomes after 1 year of front line staff implementation of the PEAK curriculum. (1st February 2018) - Dixon, Mark R.; Belisle, Jordan; Stanley, Caleb R.; Rowsey, Kyle
Abstract : Systems‐level interventions built by behavior analysts often rely on others to implement, and this may be especially true in public education settings where behavior analysts are scarce. This study evaluated the effectiveness of the Promoting the Emergence of Advanced Knowledge Direct Training (PEAK‐DT) curriculum when implemented by school teachers and direct care staff. Thirty‐nine children with autism took part in the study (19 PEAK, 15 control), where the experimental group received applied behavior analytic instruction through the PEAK‐DT curriculum, and the quasi‐randomized control group received training as usual. The PEAK‐DT assessment was first administered to the participants at the onset of the study and again following 1 year. Participants who received PEAK training gained more skills on the PEAK‐DT assessment compared to the control group (PEAK: M  = 16.0, SD  = 17.8; control: M  = 6.1, SD  = 14.4, F (1, 33) = 10.66, p  < .05), suggesting that systems level implementation of behavior analytic procedures can be effective in teaching language skills as prescribed in a packaged curriculum designed by behavior analysts.